(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2025)
Animal feed account for more than 75% total cost of production in pig industry and feed spoilage is a common factor as well as disease infection. These negative factors were influenced on production process in pig industry. Hence animal feeds and faecal samples were collected from pig farms and analyzed for microbial prevalence. The results revealed that the pathogenic microorganisms that can be zoonotic in nature E. coli staphylococcus and bacillus species of microbes were most prevalent